Analysis of genetically modified red‐fleshed apples reveals effects on growth and consumer attributes. Issue 4 (6th November 2012) - Espley, Richard V.; Bovy, Arnaud; Bava, Christina; Jaeger, Sara R; Tomes, Sumathi; Norling, Cara; Crawford, Jonathan; Rowan, Daryl; McGhie, Tony K.; Brendolise, Cyril; Putterill, Jo; Schouten, Henk J.; et al.
Summary Consumers of whole foods, such as fruits, demand consistent high quality and seek varieties with enhanced health properties, convenience or novel taste. We have raised the polyphenolic content of apple by genetic engineering of the anthocyanin pathway using the apple transcription factor MYB10. These apples have very high concentrations of foliar, flower and fruit anthocyanins, especially in the fruit peel. Independent lines were examined for impacts on tree growth, photosynthesis and fruit characteristics. Fruit were analysed for changes in metabolite and transcript levels. Fruit were also used in taste trials to study the consumer perception of such a novel apple. No negative taste attributes were associated with the elevated anthocyanins. Modification with this one gene provides near isogenic material and allows us to examine the effects on an established cultivar, with a view to enhancing consumer appeal independently of other fruit qualities.